Experimental evidence regarding CP 110 for the design of framed structures. - Salam, S. A.
Test results of ten reinforced concrete beams and five class 3 prestressed concrete beams are reported in this paper. The tests result in flexural and shear failure of under and over reinforced r.c. beams and flexural failure for psc beams having variable amount of non-tensioned steel. In all cases the results (deflection, crack initiation and propagation, ultimate strenth in bending and shear etc.) are compared with the similar provisions of the Code of Practice CP 110. The results show that the Code is conservative and in some cases of flexture failure the specimen has 100 per cent extra strength. In case of prestressed concrete class 3 structures the Code provision is inadequate for design.